Authoritarian–benevolent Leadership and its Effect on Graduate Student Creativity: The Mediating Role of Intrinsic Motivation. (13th November 2019) - Xia, Zhichen; Yang, Fan; Xu, Qingyu
Abstract: Despite numerous studies demonstrating that authoritarian leadership and benevolent leadership exert incompatible influence on an individual's creativity, the combined effects of authoritarian leadership and benevolent leadership on an individual's creativity and the related mechanisms have yet to be explained. This study tests a model that considers the combined effects of authoritarian and benevolent leadership on graduate student creativity in the universities in China, while also examining the mediating role of the intrinsic motivation of graduate students. Multisource data were collected from 297 graduate students in 60 university scientific research teams in China. The results show that when authoritarian leadership and benevolent leadership are in congruence, the intrinsic motivation of graduate students and their creativity increase as supervisor authoritarianism and benevolence increases. When authoritarian leadership and benevolent leadership are in discrepancy, the intrinsic motivation of graduate students is higher when low supervisor authoritarianism is combined with high benevolence; however, the findings also show that low authoritarian leadership combined with high benevolent leadership would not increase graduate student creativity. The relationship between authoritarian–benevolent leadership and graduate student creativity is partially mediated by intrinsic motivation. The theoretical and practical implications of the results are discussed.